Development of a Connecting Web as an Information Media for Parents of VIP Pesawat Wates Junior High School Kulon Progo - Nofianti; Hardianto, Deni; Syahrir (Formosa Journal of Sustainable Research, 2024)
This study aims to assess the feasibility and practicality of a connecting website as an information medium for parents of VIP Pesawat Junior High School students. The Research and Development (R&D) process followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). A total of 92 parents of VIP Pesawat Wates Junior High School class VII students were selected through Simple Random Sampling. Data collection involved validation questionnaires for media and material experts, and practicality surveys for parents. The data was analyzed using quantitative descriptive methods.The results show that: (1) The media validation scored 79% on two aspects—design usage and visual communication—indicating the website is feasible as an information medium. (2) The material experts' validation results were 75% for the content/material aspect, 85% for language, 75% for implementation, and 80% for usability, affirming its suitability for use. (3) In terms of practicality, user tests showed a 90% score for usefulness, 77% for ease of use, 86% for ease of learning, and 86% for satisfaction. These scores demonstrate that the connecting website is practical and effective as an information source for parents of students at VIP Pesawat Wates Junior High School